2009
DOI: 10.1037/a0014649
|View full text |Cite
|
Sign up to set email alerts
|

Weak criticisms and selective evidence: Reply to Blanton et al. (2009).

Abstract: We respond to a critique by H. Blanton et al. (2009), challenging our previous work demonstrating that an Implicit Association Test designed to assess implicit prejudice reliably predicts intergroup discrimination (A. R. McConnell & J. M. Leibold, 2001). We outline 3 flawed aspects of the critique. First, we note that claims that an outlier should be eliminated from the original data set are unfounded, and even with the elimination of this outlier, the conclusions of our original work are still strongly suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 74 publications
0
34
1
Order By: Relevance
“…That is, we found that forecasting errors were predicted by nonconscious evaluations both when we assessed this construct with the IAT in a lab setting (Study 1) and with participants' nonverbal behaviors outside of the lab (Study 2). Although converging evidence is always valuable, it is particularly worthwhile here to assuage concerns that may exist with the use of any particular measure of nonconscious evaluations, which continue to be controversial (Gawronski et al, 2008;McConnell & Leibold, 2009;Olson & Fazio, 2004;Nosek & Hansen, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, we found that forecasting errors were predicted by nonconscious evaluations both when we assessed this construct with the IAT in a lab setting (Study 1) and with participants' nonverbal behaviors outside of the lab (Study 2). Although converging evidence is always valuable, it is particularly worthwhile here to assuage concerns that may exist with the use of any particular measure of nonconscious evaluations, which continue to be controversial (Gawronski et al, 2008;McConnell & Leibold, 2009;Olson & Fazio, 2004;Nosek & Hansen, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses were conducted on the log-transformed values, but the data are reported in ms. intrusive attitudes measures. For instance, in Study 1 we chose to assess implicit attitudes with the personalized IAT, however any particular choice of attitude measure (explicit or implicit) can be contentious and subject to debate (e.g., Gawronski, Peters, & LeBel, 2008;Karpinski & Hilton, 2001;McConnell & Leibold, 2009;Olson & Fazio, 2004;Nosek & Hansen, 2008). Moreover, explicit attitude measures in general are subject to self-presentational concerns, which can cloud their interpretation (Fazio & Olson, 2003).…”
Section: Study 2: Nonverbal Leakage Predicts Affective Forecasting Ermentioning
confidence: 98%
“…Our focus here was on relative bias because no attitudes measure can be viewed in absolute terms (e.g., Bohner & Schwarz, 2001;McConnell & Leibold, 2009;Nosek, Greenwald, & Banaji, 2006). This reality, coupled with measures such as the IAT being inherently relativistic, leads us to view the current findings in terms of relative bias.…”
Section: Discussionmentioning
confidence: 99%
“…This is by no means universally accepted in the psychological literature; indeed it is currently the subject of much quite heated debate (see Blanton et al, 2006Blanton et al, , 2007Blanton et al, , 2009 for a critique of this position and Greenwald, Nosek and Sriram, 2006, McConnell and Leibold, 2009, and Ziegert and Hanges, 2009 for some rebuttals). However, it would seem that in some domains, this notion of implicit attitudes, deriving from various associative connections and operating unconsciously alongside our more reflective attitudes (and indeed conflicting with them on occasion), might have some credibility (Beattie, 2013: Kahneman, 2011.…”
Section: Discussionmentioning
confidence: 99%